ABOUT THE UFA PERIOD IN THE HISTORY OF THE MOSCOW PETROLEUM INSTITUTE NAMED AFTER I.M. GUBKIN - Ildus G. Ibragimov; Oleg A. Baulin; Ferdinand Sh. Zabirov (Высшее образование в России)
The authors provide information about the Ufa period in the history of the Moscow Petroleum Institute named after I.M. Gubkin, which in April 2015 marks the its 85th anniversary. For the first time in one article the authors present a summary of the structure and the head of the Ufa branch of the Moscow Petroleum Institute, note their achievements in the development of an educational institution in the difficult war and postwar years. It is shown that the current achievements of the Ufa State Petroleum Technological University are the result of the traditions established by the selfless work of team staff of the Ufa branch of the Moscow Petroleum Institute.